2003
DOI: 10.1038/sj.onc.1206838
|View full text |Cite|
|
Sign up to set email alerts
|

Epstein–Barr virus can inhibit genotoxin-induced G1 arrest downstream of p53 by preventing the inactivation of CDK2

Abstract: Epstein-Barr virus (EBV) is involved in the pathogenesis of several B cell lymphoproliferations, but the precise contribution it makes to the aetiology of each remains unclear. In vitro, the virus has potent growth transforming activity and efficiently induces the continuous proliferation of normal human B cells. A comparison of EBVinfected primary B cells with an isogenic population induced to proliferate by CD40-ligand (CD40L) and IL4 has revealed that EBV can override -by a novel mechanism -the p53/pRb-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 41 publications
3
38
1
Order By: Relevance
“…EBVpositive BL41/B95.8 cells also accumulated with apparently normal nuclei and 4N DNA content. This indicated that EBV is unable to overcome the G 2 /M arrest after irradiation and is consistent with the results from previous experiments using EBV-immortalized LCLs (5,21).…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…EBVpositive BL41/B95.8 cells also accumulated with apparently normal nuclei and 4N DNA content. This indicated that EBV is unable to overcome the G 2 /M arrest after irradiation and is consistent with the results from previous experiments using EBV-immortalized LCLs (5,21).…”
Section: Resultssupporting
confidence: 81%
“…Although the tumor suppressor p53 is one of the major targets of oncogenic viruses, several studies have shown that EBV does not specifically target p53 during the transformation of normal B cells into LCLs (1, 2). Nevertheless, recent studies demonstrated that although not able to directly target p53, EBV may still interfere with cell cycle checkpoints at both G 1 /S and G 2 /M phases (15,21,31).…”
Section: Epstein-barr Virus (Ebv) Is a Gammaherpesvirus That Pro-mentioning
confidence: 99%
See 2 more Smart Citations
“…Both transmissible (Bernheim et al, 1981;Klein, 1986) and unstable chromosomal aberrations (Stollmann et al, 1985;Zattara-Cannoni et al, 1996;Chan et al, 2001) are present in EBV-associated malignancies, but the contribution of the virus to this phenotype is not understood. It was suggested that EBV might prime genomic instability by activating specific recombinases (Kuhn-Hallek et al, 1995) by integration (Jox et al, 1997) or by induction of oxidative stress (Gualandi et al, 2001), whereas latent viral genes such as LMP1 and LMP2 could contribute by modulating telomere function and DNA repair Liu et al, 2005), or by enhancing the sensitivity to DNAdamaging agents (O'Nions and Allday, 2003;Liu et al, 2004). However, there is no conclusive evidence for the mutagenic potential of the virus.…”
Section: Introductionmentioning
confidence: 99%